An evaluation of group activity schedules to promote social play in children with autism. Issue 3 (14th May 2018) - Akers, Jessica S.; Higbee, Thomas S.; Gerencser, Kristina R.; Pellegrino, Azure J.
Abstract : Children with autism spectrum disorder (ASD) often have deficits in social skills and may avoid engaging in play activities with typically developing peers. The purpose of this study was to identify the utility of activity schedules, with embedded scripts, to teach three children with ASD to play a complex social game. Specifically, children with ASD were taught to play hide‐and‐seek with typically developing peers. Once the activity schedules were introduced, participants began engaging in independent hide‐and‐seek behaviors. A secondary purpose of this study was to systematically fade the activity schedules to the least intrusive version. We faded all of the scripts and the majority of activity schedule components for the three participants. Participants continued to play hide‐and‐seek with the faded versions of the schedules in a novel environment and 2 weeks after treatment concluded.